COVID-19 and the Vasculature: Current Aspects and Long-Term Consequences - Martínez-Salazar, Berenice; Holwerda, Melle; Stüdle, Chiara; Piragyte, Indre; Mercader, Nadia; Engelhardt, Britta; Rieben, Robert; Döring, Yvonne (Frontiers in Cell and Developmental Biology, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first identified in December 2019 as a novel respiratory pathogen and is the causative agent of Corona Virus Disease 2019 (COVID-19). Early on during this pandemic, it became apparent that SARS-CoV-2 was not only restricted to infecting the respiratory tract, but the virus was also found in other tissues, including the vasculature. Individuals with underlying pre-existing co-morbidities like diabetes and hypertension have been more prone to develop severe illness and fatal outcomes during COVID-19. In addition, critical clinical observations made in COVID-19 patients include hypercoagulation, cardiomyopathy, heart arrythmia, and endothelial dysfunction, which are indicative for an involvement of the vasculature in COVID-19 pathology. Hence, this review summarizes the impact of SARS-CoV-2 infection on the vasculature and details how the virus promotes (chronic) vascular inflammation. We provide a general overview of SARS-CoV-2, its entry determinant Angiotensin-Converting Enzyme II (ACE2) and the detection of the SARS-CoV-2 in extrapulmonary tissue. Further, we describe the relation between COVID-19 and cardiovascular diseases (CVD) and their impact on the heart and vasculature. Clinical findings on endothelial changes during COVID-19 are reviewed in detail and recent evidence from in vitro studies on the susceptibility of endothelial cells to SARS-CoV-2 infection is discussed. We conclude with current notions on the contribution of cardiovascular events to long term consequences of COVID-19, also known as “Long-COVID-syndrome”. Altogether, our review provides a detailed overview of the current perspectives of COVID-19 and its influence on the vasculature.